Screening Lung Cancer in Sampang Regency, Madura Through Empowerment and Health Cadres Formation - Yudhawati, Resti; Wulandari, Laksmi; Febriani, Anna; Wati, Farah Fatma; Thendeyas, Richar Tomy; Atik, Nurul; Hariputri, Wulan Rahmawati; Novananda, Donny Ardika; Riyanto, Shandy Billy (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Treatment for lung cancer remains challenging since most of the patients seek medical advice at an advanced stage of disease. Sampang is one of the regencies that refers many lung cancer patients in late stages to Dr. Soetomo Hospital, Surabaya, due to lack of information of lung cancer and early detection. Limited number of health workers to deliver comprehensive education to all areas requires community volunteers to fill this gap. The objective of this study was to educate and promote lung cancer awareness to the health cadres in Sampang as well as training them to early detecting individuals in the community with high-risk factors, as an attempt to bridge between the health workers and community, therefore the number of lung cancer early detection may be improved. Early identification of cancer may result in reduced morbidity and mortality, and in some cases, if detected early enough, therapy may involve only surgery.  The education was provided for the health cadres by providing information related to lung cancer and guidance to fill the questionnaire and scoring of lung cancer risk factors. The participants' understanding was measured using a pretest-posttest design. Thirty health cadres have been successfully formed, and they have gained knowledge of lung cancer and mastered capability to perform early-screening of lung cancer in the community as shown by the increase of post-test result compared to pre-test. The health cadres then implemented their knowledge of lung cancer early-screening by distributing questionnaires of lung cancer risk factor scoring to residents using door to door methods. The questionnaires’ evaluation collected by the health cadres showed that there were 93 residents with high-risk factors of lung cancer.  In conclusion, the health cadres has been capable to detect high-risk factors individuals in the community which further be followed up by community health workers comprehensively.